The Influence of Heuristic judgments in Social Media on Corporate Reputation: A Study in Spanish Leader Companies - Cerdá Suárez, Luis Manuel; Perán López, Jesús; Cambronero Saiz, Belén (Sustainability, 2020)
rom a corporate-side perspective, the communication of reputational actions and news of companies becomes critical for success. However, in communication, business, and management studies, heuristics can be understood as simple cognitive processes that allow assessments, predictions, and decisions to be made quickly and efficiently by consumers and economic agents. This aspect can sometimes lead to cognitive biases, especially when little information is available or in situations of high uncertainty. The aim of this research is to investigate the influence of heuristic judgments in social media on corporate reputation ratings obtained in Spanish leader companies. Using data collected in Spain, this paper analyzes the influence of heuristics concerning news items on corporate reputation, measured by the Monitor Empresarial de Reputacion Corporativa (MERCO) Index. The main finding of this paper is that the total number of news items has a positive effect on corporate reputation, particularly in the categories of culture-values, results/image, expansion, and sponsorship/donations. Additionally, this work serves as a repository of knowledge applicable to similar situations considering the specificities of each particular case. The importance to intervene on certain variables at different levels of managerial performance is described and implications for companies are discussed in these pages.
Keywords: information processing; stakeholders; corporate reputation; heuristics; social media; Scopus; JCR